Dynamics of Education on the Indonesia-Malaysia Border: An Ethnopedagogical Study Analysis - Ramadhan, Iwan; Imran, Imran; Hardiansyah, Muhammad Agus (Journal of Nonformal Education, 2024)
This research examines education dynamics in the border region between Indonesia and Malaysia, specifically in Bengkyang Regency. The study focuses on the challenges of maintaining cultural identity and nationalism amidst the strong influence of foreign cultures. The educational units comprise one kindergarten, 18 elementary schools, six junior high schools, one senior high school, and three vocational schools. In Jagoi Babang, there is one private kindergarten, two private elementary schools, one private junior high school, and two private vocational schools. Only a few schools include vision and mission statements aimed at building and maintaining nationalism. This study explores educational practices and the role of Ethno pedagogy in strengthening nationalism among students. Using a qualitative research method with an ethnopedagogical approach, the research team analyzed education dynamics at the border through ethnopedagogical studies. The results indicate that special attention is still needed for local genius and local wisdom through the articulation of cultural values, as educational practices in various domains emphasize local wisdom as a source of innovation and skills that can be empowered for community welfare. The local wisdom relates to how knowledge is generated, stored, applied, and managed. In supporting the success of core learning in schools, information obtained from students reveals that obstacles such as facilities and infrastructure and gaps in learning during class hours are still frequently experienced by students. The research findings show that schools in Jagoi Babang suffer from a lack of facilities and infrastructure, hindering access to education. Additionally, the integration of local values into the curriculum needs to be higher, contributing to the degradation of local culture. The study finds that despite efforts to build nationalism, the lack of innovation in teaching methods remains a barrier. There is a need for government attention to improve the quality of education and infrastructure. The novelty of this research lies in its emphasis on the role of Ethno pedagogy in education in border areas, providing valuable insights for policymakers and educators in designing more effective programs to support education and strengthen national identity.